2018
DOI: 10.3389/fphar.2018.01457
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen Induces Developmental Toxicity in Zebrafish Embryos/Larvae Through Oxidative Stress, Apoptosis, and Energy Metabolism Disorder

Abstract: Psoralen toxicity is an issue of wide concern. However, an assay for psoralen-induced developmental toxicity has not been reported to date. Moreover, the underlying mechanism of psoralen-induced developmental toxicity is unclear. Therefore, this study attempted to develop a psoralen-induced developmental toxicity assay in zebrafish embryos/larvae. Psoralen treatment caused a decrease in the hatching rate and body length and a significant increase in the malformation rate of zebrafish. Yolk retention, pericardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 39 publications
5
43
0
1
Order By: Relevance
“…Zebrafish (Danio rerio) has been widely accepted as a prominent vertebrate model for toxicological and developmental studies in recent years because of the high fecundity, rapid organogenesis, short generation, and transparent body of embryos and larvae, and so on (Hill et al, 2005;McGrath and Li, 2008;Haque and Ward, 2018;Xia et al, 2018;Al-Samadi et al, 2019;Van Sebille et al, 2019). In addition, it shares high degree of genetic conservation which makes it have additional advantages over traditional animal models (Crawford et al, 2008;Jia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish (Danio rerio) has been widely accepted as a prominent vertebrate model for toxicological and developmental studies in recent years because of the high fecundity, rapid organogenesis, short generation, and transparent body of embryos and larvae, and so on (Hill et al, 2005;McGrath and Li, 2008;Haque and Ward, 2018;Xia et al, 2018;Al-Samadi et al, 2019;Van Sebille et al, 2019). In addition, it shares high degree of genetic conservation which makes it have additional advantages over traditional animal models (Crawford et al, 2008;Jia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several morphological abnormalities such as the yolk retention, swim-bladder deficiency, pericardial oedema, and curved body shape were observed at 24 to 96 hpf in psoralen-treated embryos. Also, it was observed that psoralen exerted toxic effects on the developing heart, liver, phagocytes, and nervous system [40]. Increased generation of reactive oxygen species and malondialdehyde concentrations and inhibition of total superoxide dismutase activity in the zebrafish embryo indicate oxidative stress caused by the psoralen [40].…”
Section: Resultsmentioning
confidence: 99%
“…GA at 0.5–1.0 μ M exhibited specific fin developmental defect with the phenotype resembling those caused by thalidomide. The amount of GA absorbed by the zebrafish embryos appeared to be time dependent [40]. It was further revealed GA upregulated ALDH12 (Aldehyde Dehydrogenase 1 Family Member A2) and downregulated CYP26A1 (cytochrome P450 family 26 subfamily A member 1) at 8hpf.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, down-regulated expression levels of ppara1, fas, and hmgcra demonstrated psoralen-induced abnormal lipid metabolism, causing zebrafish embryo/larval developmental toxicity, reducing the rate of hatching in zebrafish, diminishing their body length, and significantly increasing the rate of deformity. Because the yolk is the only source of energy during zebrafish embryo development, yolk retention, pericardial edema, fish sting defects, and flexion were observed in zebrafish larvae, in addition to toxic effects to the developing heart, liver, phagocytes, and nervous system (Xia et al, 2018). The BeWo human placental cell line is derived from choriocarcinoma and is used as a rate-limiting barrier model for drug and nutrient exchange between mother and fetus in the placenta (Hawkins et al, 2018;Zhang et al, 2020).…”
Section: Embryotoxicitymentioning
confidence: 99%